THE FERMI ENERGY OF Ni, Cr, Zn AND THE ELECTROCATALYTIC ACTIVITY OF THE TRIPLE ALLOYS ON THE BASE OF THESE METALS - A. D. Andreyanov (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
It was established the correlation of the electrocatalytic activity of alloys Ni-Cr-Zn at the variable contents of zinc with values of Fermy energy of their components. Electrocatalytic activity of alloys was estimated by density of the current, determined by extrapolation of Tafel straight lines, constructed on the basis of polarizing curve alloys Ni-Cr-Zn investigated by the method of suspended half-element. For Fermy energy calculation of various metals Sommerfeld model, in which distribution of electrons by speed is described by Fermi—Dirac statistic was used.